A qualitative exploration of the downstream impact of a sustained disruption to the methadone supply in Mexico: effects on the mental, financial, and social health of patients with opioid use disorder in TijuanaResearch in context - Annick Bórquez; Jesse Lloyd Goldshear; Sheryl Muñoz-Mina; Arturo Tornez; Alicia Harvey Vera; María Elena Medina Mora; Gudelia Rangel; Steffanie A. Strathdee (The Lancet Regional Health. Americas, 2025)
Summary: Background: Medications for opioid use disorder (MOUD) are considered the gold standard long-term treatment for opioid use disorder (OUD) as they have a range of health and psycho-social benefits. Sudden reduction or interruptions in MOUD can have both immediate and long-term consequences for patients. We sought to qualitatively examine the impact of the prolonged closure of Mexico’s main methadone production facility (Psicofarma) in 2023 on MOUD patients in Tijuana, Mexico. Methods: We conducted semi-structured qualitative interviews with 20 MOUD patients in Tijuana, Mexico, from May to August 2023. We transcribed interviews and translated them from Spanish to English for analysis. Our analysis followed a thematic and narrative approach, and code congruency was found by consensus. Analytic and narrative memos provided the foundation for the ultimate findings. Findings: The closure of Psicofarma resulted in a sudden stoppage in MOUD for participants. While some were provided with a benzodiazepine alternative and/or psychotherapy by their clinics, most were completely cut off from medical support. Participants reported returning to the illicit market for solutions to both withdrawal and drug cravings. Increased spending on the illicit market drained participant finances and strained employment and familial relationships. Interpretation: The sudden interruption of MOUD treatment had varied yet predictable effects on our participants. These results demonstrate the need to ensure adequate methadone supply for people with OUD in Mexico and to offer other alternative therapies such as low-threshold buprenorphine. Funding: Support for this study was provided by NIDA (R01DA049644-S4, T32DA023356 and DP2DA049295).